COMPETENCES OF TEACHING ENGLISH PHONETICS TO UNIVERSITY STUDENTS (Conference Zone, 2022)
English has become a global language not only because it is spoken by so many people worldwide, but also because it has evolved into the primary tool for international communication, enabling access to the knowledge and technological resources of the whole planet. The abilities of teaching English phonetics to university students are covered in this article.